2020
DOI: 10.15407/fz66.05.073
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Proteasomes

Abstract: Little-known to a wide range of specialists details of the functioning of one of the main participants in cellular metabolism – a complex of neutral proteases with their regulators, which is called “proteasome” – are observed in this paper. The review analyzes the works of recent years devoted to the study of the participation of proteasomes in intercellular signaling and catabolism of regulatory and signaling proteins in the extracellular space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
(93 reference statements)
0
1
0
Order By: Relevance
“…It is known that white blood cells secrete exosomes containing proteasomes in the form of 20S particles [2]. It was found that proteasomal activity is important not only for intracellular proteolysis, as proved by the presence of functional proteasomes in blood plasma, alveolar fluid, and in the culture medium of some cells [3,4]. The process of ubiquitination and the work of the proteasomal system are important for the development of tissues and organs and the maintenance of cellular homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that white blood cells secrete exosomes containing proteasomes in the form of 20S particles [2]. It was found that proteasomal activity is important not only for intracellular proteolysis, as proved by the presence of functional proteasomes in blood plasma, alveolar fluid, and in the culture medium of some cells [3,4]. The process of ubiquitination and the work of the proteasomal system are important for the development of tissues and organs and the maintenance of cellular homeostasis.…”
Section: Introductionmentioning
confidence: 99%